Biochar-zero-valent iron composite material for efficiently removing radionuclides in aquatic products and preparation method of biochar-zero-valent iron composite material
By using special biochar-nano zero-valent iron composites, the problems of low efficiency, high cost and great environmental impact in aquatic products are solved, and efficient, low cost and environmentally friendly removal effects are achieved, providing a wide range of application prospects for aquatic product processing and environmental monitoring around nuclear energy facilities.
Patent Information
- Application Number
- CN202510058713.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art has shortcomings in the removal of radionuclides of aquatic products, such as treatment effects, operating costs and environmental impacts, and it is difficult to effectively solve the problem of radionuclide pollution in aquatic products.
A composite material of biochar and nano-zero-valent iron is used to prepare composite materials with optimized specific surface area, pore volume and pore size characteristics through a specific preparation process. The high adsorption performance of biochar and the strong reduction properties of nano-zero-valent iron are used to achieve efficient removal of radionuclides in aquatic products.
It has achieved efficient removal efficiency of radionuclides in aquatic products to reach more than 90%, reducing operating costs and environmental impacts, and has a wide range of raw materials and low cost, which is suitable for applications in the fields of aquatic product processing and environmental monitoring around nuclear energy facilities.
Smart Images

Figure BDA0005242219550000131 
Figure BDA0005242219550000141 
Figure BDA0005242219550000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products and a preparation method thereof. Background Art
[0002] With the widespread application of nuclear energy technology and the increase in nuclear energy facilities, the pollution problem of radionuclides in the environment is becoming increasingly serious, especially in the field of aquatic products. Radionuclides enter aquatic products through water, soil and other channels, posing a potential threat to human health.
[0003] At present, traditional methods for removing radioactive nuclides from aquatic products include chemical precipitation, ion exchange, adsorption and other methods. However, the above methods have many shortcomings in terms of treatment effect, operating cost, environmental impact and other aspects. For example, although chemical precipitation can remove some radioactive nuclides, the resulting precipitate is difficult to handle and easily causes secondary pollution. Although the ion exchange method has a high removal efficiency, the regeneration and disposal cost of the resin is relatively high. Although the adsorption method is simple to operate, the performance of the adsorption material directly affects the removal effect, and it is difficult to regenerate and reuse.
[0004] To this end, those skilled in the art have proposed a biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products and a preparation method thereof to solve the problems raised by the background technology. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products and a preparation method thereof, so as to solve the problems that the methods for removing radioactive nuclides from aquatic products in the prior art have many shortcomings in treatment effect, operating cost, environmental impact, etc.
[0006] A biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products, the composite material consists of biochar and nano-zero-valent iron loaded on the biochar, wherein the biochar is prepared by cracking wheat straw at 600-700°C for 2-3 hours, then soaking in a 0.5-1M acid solution for 12-24 hours, washing with distilled water to neutrality, and drying at 80-105°C for 6-12 hours, the nano-zero-valent iron is prepared by reacting a ferrous sulfate solution with a carboxymethyl cellulose solution and a sodium borohydride solution under nitrogen protection, and loaded on the biochar, and the specific surface area of the composite material is 6-12 m 2 / g, pore volume is 0.01~0.04cm 3 / g, and the average pore size is 8-15nm.
[0007] Preferably, the loading of nano zero-valent iron on biochar is achieved by the following steps: adding carboxymethyl cellulose solution to ferrous sulfate solution, adding biochar after uniform mixing, and then dropping sodium borohydride solution, under continuous stirring conditions, passing nitrogen for 30 to 60 minutes and then stopping the nitrogen flow, sealing the reaction for 60 to 90 minutes and then stopping stirring, standing in the dark at room temperature 20 to 25°C for 6 to 12 hours, and separating by magnetic separation to obtain a biochar nano zero-valent iron composite material.
[0008] Preferably, a layer of mesoporous material is first loaded on the surface of biochar, and then nano zero-valent iron is loaded thereon to increase the specific surface area and pore volume of the composite material, thereby enhancing the adsorption capacity of radionuclides. The specific steps include:
[0009] S1.1. Select appropriate mesoporous materials, including silica and alumina, and evenly coat them on the surface of biochar;
[0010] S1.2, by chemical or physical methods, nanometer zero-valent iron is loaded on the mesoporous material to form a multi-level structure composite material;
[0011] S1.3. Characterize the composite material, including determination of specific surface area, pore volume, and pore size parameters;
[0012] At the same time, by adopting the gradient loading technology, the distribution of nano zero-valent iron on the biochar presents a gradient change, so as to improve the removal efficiency of the composite material for radionuclides of different sizes and types. The specific steps include:
[0013] S2.01, dispersing the biochar in a suitable solvent to form a uniform suspension;
[0014] S2.02, gradually adding nano-zero-valent iron solutions of different concentrations to make the nano-zero-valent iron present a gradient distribution on the biochar;
[0015] S2.03. Dry and cure the composite material to improve its stability.
[0016] Preferably, other metal elements (including palladium, nickel, etc.) are introduced into nano zero-valent iron to form bimetallic nanoparticles to improve its catalytic activity and ability to reduce radioactive nuclides. The specific steps include:
[0017] S2.1. Evenly mix an appropriate amount of metal salt solution (including palladium salt, nickel salt, etc.) and ferrous sulfate solution;
[0018] S2.2, under nitrogen protection, reacting the mixed solution with a carboxymethyl cellulose solution and a sodium borohydride solution to prepare bimetallic nanoparticles;
[0019] S2.3. Loading bimetallic nanoparticles on biochar to form a composite material.
[0020] At the same time, the surface of nano zero-valent iron is modified, including the use of surfactants and polymers, to improve its dispersibility and stability in aquatic products and prevent agglomeration. The specific steps include:
[0021] S2.01, select suitable surfactants or polymers, including sodium lauryl sulfate and polyvinyl alcohol;
[0022] S2.02, dissolving the surfactant or polymer in a suitable solvent, and mixing the mixture with the nano zero-valent iron solution;
[0023] S2.03. Load the mixed solution onto biochar and tightly combine the surfactant or polymer with the nano zero-valent iron through physical or chemical methods.
[0024] Preferably, the preparation of biochar adopts a new pyrolysis technology, by introducing plasma pyrolysis and laser pyrolysis technology to prepare biochar with special structure and properties, including high specific surface area and high porosity, and the specific steps include:
[0025] S3.1. Select appropriate biomass raw materials, including bamboo and corn stalks;
[0026] S3.2. Using plasma pyrolysis or laser pyrolysis technology to pyrolyze biomass raw materials into biochar;
[0027] S3.3. Characterize the biochar, including determination of elemental composition and structural characteristic parameters.
[0028] Preferably, the composite material is prepared by continuous preparation technology, integrating the steps of biochar cracking, nano zero-valent iron preparation and loading to improve production efficiency. The specific steps include:
[0029] S4.1. Design and build a continuous preparation device, including a biomass cracking unit, a nano zero-valent iron preparation unit and a loading unit;
[0030] S4.2, sending the biomass raw material into a cracking unit for cracking to obtain biochar;
[0031] S4.3, sending the biochar into the nano zero-valent iron preparation unit for loading to obtain a composite material;
[0032] S4.4. Perform subsequent processing on the composite material, including drying and curing.
[0033] Preferably, the removal efficiency of the composite material for radionuclides reaches more than 90%.
[0034] A method for preparing a biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products, using the above-mentioned biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products, comprising:
[0035] Step 1, preparation of biochar: First, wheat straw is selected as a biomass raw material, and cracked at 600-700°C for 2-3 hours; after the cracking is completed, the biochar is soaked in a 0.5-1M acid solution for 12-24 hours to remove impurities; then, the biochar is washed with distilled water until neutral, and dried at 80-105°C for 6-12 hours to obtain the prepared biochar;
[0036] Step 2, preparation of nano zero-valent iron: mix ferrous sulfate solution and carboxymethyl cellulose solution in a certain proportion. Carboxymethyl cellulose, as a stabilizer, helps prevent the agglomeration of nano zero-valent iron particles. Then, in a nitrogen-protected environment, slowly add sodium borohydride solution for reduction reaction to generate nano zero-valent iron. During the reaction, continuous stirring is required to ensure the uniform generation of nano zero-valent iron, while controlling the reaction temperature and speed to obtain the ideal nanoparticle size and distribution. In addition, in order to further improve the stability and activity of nano zero-valent iron, an appropriate amount of reducing agent or surface modifier, such as polyvinyl pyrrolidone (PVP), etc., can be added to the reaction system to optimize the performance of nano zero-valent iron.
[0037] Step 3: Nano-zero-valent iron is loaded on biochar: the prepared biochar is added to a mixed solution of ferrous sulfate and carboxymethyl cellulose, mixed evenly, and then a sodium borohydride solution is added dropwise; under continuous stirring, nitrogen is introduced for 30 to 60 minutes and then stopped, and the reaction is sealed for 60 to 90 minutes; thereafter, the mixture is allowed to stand at room temperature of 20 to 25°C in the dark for 6 to 12 hours, and the biochar-nano-zero-valent iron composite material is separated by magnetic separation;
[0038] Step 4, preparation of multi-level structure composite materials: In order to increase the specific surface area and pore volume of the composite material and enhance its adsorption capacity for radioactive nuclides, firstly, a layer of mesoporous material is loaded on the surface of biochar; mesoporous materials with excellent pore structures such as silica and alumina are selected, and they are uniformly coated on the surface of biochar by sol-gel method, impregnation method or chemical vapor deposition method; then, nano zero-valent iron is loaded on the mesoporous material by chemical or physical methods (such as co-precipitation method, impregnation reduction method, etc.) to form a multi-level structure composite material; this multi-level structure not only increases the specific surface area and pore volume of the composite material, but also improves the dispersibility and stability of nano zero-valent iron through the confinement effect of the mesoporous material, thereby improving the overall performance of the composite material;
[0039] Step 5: Application of gradient loading technology: To further improve the removal efficiency of composite materials for radionuclides of different sizes and types, gradient loading technology is used; first, the biochar is dispersed in an appropriate solvent (such as ethanol, water, etc.) to form a uniform suspension; then, nano-zero-valent iron solutions of different concentrations are gradually added, and the nano-zero-valent iron is distributed in a gradient on the biochar by controlling the addition speed and stirring conditions; this gradient distribution can more effectively utilize the pore structure of biochar and the reduction performance of nano-zero-valent iron to remove radionuclides of different sizes and types in a targeted manner; after the loading is completed, the composite material is dried and cured to improve its stability and durability;
[0040] Step 6. Preparation and loading of bimetallic nanoparticles: In order to improve the catalytic activity of nano zero-valent iron and its ability to reduce radioactive nuclides, other metal elements (such as palladium, nickel, etc.) are introduced to form bimetallic nanoparticles; first, an appropriate amount of metal salt solution (such as palladium salt, nickel salt, etc.) is evenly mixed with ferrous sulfate solution; then, under nitrogen protection, the mixed solution is reacted with carboxymethyl cellulose solution and sodium borohydride solution to prepare bimetallic nanoparticles; during the reaction, the reaction conditions and metal ratios need to be precisely controlled to obtain an ideal bimetallic nanoparticle structure; after preparation, the bimetallic nanoparticles are loaded on biochar by physical or chemical methods to form a composite material with the ability to efficiently remove radioactive nuclides; this bimetallic nanoparticle not only improves the catalytic activity of the composite material, but also enhances its ability to reduce and remove radioactive nuclides through a synergistic effect;
[0041] Step 7: Surface modification of nano zero-valent iron: In order to prevent the aggregation of nano zero-valent iron and improve its dispersibility and stability in aquatic products, the nano zero-valent iron is surface modified; a suitable surfactant or polymer (including sodium dodecyl sulfate, polyvinyl alcohol) is selected and dissolved in an appropriate solvent, mixed evenly with the nano zero-valent iron solution and loaded on the biochar;
[0042] Step 8: Prepare biochar using new pyrolysis technology: In order to improve the performance of biochar, plasma pyrolysis or laser pyrolysis technology is used to prepare biochar; biomass raw materials such as bamboo and corn stalks are selected for pyrolysis, and the obtained biochar is characterized to determine its elemental composition and structural characteristics;
[0043] Step 9. Application of continuous preparation technology: In order to improve production efficiency, the steps of biochar cracking, nano zero-valent iron preparation and loading are integrated together for continuous preparation; design and build a continuous preparation device, including a biomass cracking unit, a nano zero-valent iron preparation unit and a loading unit, to achieve continuous production of composite materials.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1. The present invention adopts a composite material of biochar and nano-zero-valent iron, utilizes the high specific surface area and rich pore structure of biochar, and the strong reducing property of nano-zero-valent iron, to achieve efficient removal of radioactive nuclides in aquatic products; at the same time, experimental results show that the removal efficiency of radioactive nuclides by the composite material reaches more than 90%, which is significantly better than traditional methods.
[0046] 2. The composite material of the present invention can be prepared from a wide range of raw materials, such as biomass resources such as wheat straw, with low cost, simple preparation process and easy operation; at the same time, the composite material does not require complicated equipment and processes during use, reducing processing costs.
[0047] 3. The biochar of the present invention, as a biomass cracking product, has excellent adsorption performance and stability and can be recycled; nano zero-valent iron is consumed during the reaction, but its reduction product is harmless to the environment; therefore, the composite material of the present invention has little impact on the environment while removing radioactive nuclides from aquatic products, and meets the requirements of sustainable development.
[0048] 4. The composite material of the present invention shows good removal effect on different types of radionuclides and has no adverse effect on the quality and taste of aquatic products; therefore, the composite material has broad application prospects in the fields of aquatic product processing, environmental monitoring around nuclear power facilities, etc. DETAILED DESCRIPTION
[0049] The following examples are used to illustrate the present invention, but they are not intended to limit the scope of the present invention.
[0050] Embodiment: The present invention provides a biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products. The composite material consists of biochar and nano-zero-valent iron loaded on the biochar. The biochar is prepared by cracking wheat straw at 600-700°C for 2-3 hours, soaking in a 0.5-1M acid solution for 12-24 hours, washing with distilled water to neutrality, and drying at 80-105°C for 6-12 hours. The nano-zero-valent iron is prepared by reacting a ferrous sulfate solution with a carboxymethyl cellulose solution and a sodium borohydride solution under nitrogen protection, and loaded on the biochar. The specific surface area of the composite material is 6-12 m 2 / g, pore volume is 0.01~0.04cm 3 / g, average pore size is 8-15nm;
[0051] Nano-zero-valent iron is loaded on biochar through the following steps: carboxymethyl cellulose solution is added to ferrous sulfate solution, biochar is added after uniform mixing, and sodium borohydride solution is added dropwise. Under continuous stirring conditions, nitrogen is introduced for 30 to 60 minutes and then the nitrogen is stopped. The reaction is sealed and stopped after 60 to 90 minutes. The mixture is allowed to stand in the dark at room temperature of 20 to 25°C for 6 to 12 hours, and the biochar nano-zero-valent iron composite material is separated by magnetic separation.
[0052] From the above, it can be seen that the biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products is a biochar and nano zero-valent iron composite material prepared by a specific process. It has optimized specific surface area, pore volume and pore size characteristics, and can significantly improve the adsorption and removal efficiency of radioactive nuclides. It provides a new technical guarantee for the safety of aquatic products and demonstrates excellent environmental purification performance and practical application potential.
[0053] Furthermore, a layer of mesoporous material is first loaded on the surface of the biochar, and then nano-zero-valent iron is loaded thereon to increase the specific surface area and pore volume of the composite material, thereby enhancing the adsorption capacity of radionuclides. The specific steps include:
[0054] S1.1. Select appropriate mesoporous materials, including silica and alumina, and evenly coat them on the surface of biochar;
[0055] S1.2, by chemical or physical methods, nanometer zero-valent iron is loaded on the mesoporous material to form a multi-level structure composite material;
[0056] S1.3. Characterize the composite material, including determination of specific surface area, pore volume, and pore size parameters;
[0057] At the same time, by adopting the gradient loading technology, the distribution of nano zero-valent iron on the biochar presents a gradient change, so as to improve the removal efficiency of the composite material for radionuclides of different sizes and types. The specific steps include:
[0058] S2.01, dispersing the biochar in a suitable solvent to form a uniform suspension;
[0059] S2.02, gradually adding nano-zero-valent iron solutions of different concentrations to make the nano-zero-valent iron present a gradient distribution on the biochar;
[0060] S2.03. Dry and cure the composite material to improve its stability.
[0061] From the above, we can see that by first loading a layer of mesoporous material on the surface of biochar, then loading nano zero-valent iron on it, and innovatively adopting gradient loading technology, not only the specific surface area and pore volume of the composite material are significantly improved, and its adsorption capacity for radioactive nuclides is enhanced, but also through gradient distribution, the composite material can more efficiently remove radioactive nuclides of different sizes and types, providing a more accurate and efficient solution for the treatment of radioactive contamination of aquatic products, showing excellent technical advantages and application prospects.
[0062] Furthermore, other metal elements (including palladium, nickel, etc.) are introduced into the nano zero-valent iron to form bimetallic nanoparticles to improve its catalytic activity and ability to reduce radioactive nuclides. The specific steps include:
[0063] S2.1. Evenly mix an appropriate amount of metal salt solution (including palladium salt, nickel salt, etc.) and ferrous sulfate solution;
[0064] S2.2, under nitrogen protection, reacting the mixed solution with a carboxymethyl cellulose solution and a sodium borohydride solution to prepare bimetallic nanoparticles;
[0065] S2.3. Loading bimetallic nanoparticles on biochar to form a composite material.
[0066] At the same time, the surface of nano zero-valent iron is modified, including the use of surfactants and polymers, to improve its dispersibility and stability in aquatic products and prevent agglomeration. The specific steps include:
[0067] S2.01, select suitable surfactants or polymers, including sodium lauryl sulfate and polyvinyl alcohol;
[0068] S2.02, dissolving the surfactant or polymer in a suitable solvent, and mixing the mixture with the nano zero-valent iron solution;
[0069] S2.03. Load the mixed solution onto biochar and tightly combine the surfactant or polymer with the nano zero-valent iron through physical or chemical methods.
[0070] From the above, it can be seen that by introducing palladium, nickel and other metal elements into nano zero-valent iron to form bimetallic nanoparticles, the catalytic activity of the composite material and its ability to reduce radioactive nuclides are significantly improved; at the same time, by surface modification of nano zero-valent iron, its dispersibility and stability in aquatic products are effectively improved, and the occurrence of agglomeration is prevented; together, the removal efficiency and application performance of the composite material for radioactive nuclides are enhanced, providing a more efficient and stable solution for the control of radioactive pollution of aquatic products, which has important technological breakthroughs and practical application value.
[0071] Furthermore, the preparation of biochar adopts a new pyrolysis technology, by introducing plasma pyrolysis and laser pyrolysis technology, to prepare biochar with special structure and properties, including high specific surface area and high porosity. The specific steps include:
[0072] S3.1. Select appropriate biomass raw materials, including bamboo and corn stalks;
[0073] S3.2. Using plasma pyrolysis or laser pyrolysis technology to pyrolyze biomass raw materials into biochar;
[0074] S3.3. Characterize the biochar, including determination of elemental composition and structural characteristic parameters.
[0075] From the above, we can see that by using new pyrolysis technologies such as plasma pyrolysis or laser pyrolysis technology to prepare biochar, biochar with higher specific surface area and high porosity can be prepared; the improvement of these special structures and properties significantly enhances the adsorption capacity, catalytic activity and removal efficiency of radionuclides of biochar; at the same time, the application of new pyrolysis technology has also broadened the selection range of biomass raw materials, improved the preparation efficiency and product quality of biochar, and laid a solid foundation for the widespread application of biochar in environmental governance, energy conversion and other fields; and provided strong support for the sustainable development of related industries.
[0076] Furthermore, the composite material preparation adopts a continuous preparation technology, integrating the steps of biochar pyrolysis, nano zero-valent iron preparation and loading to improve production efficiency. The specific steps include:
[0077] S4.1. Design and build a continuous preparation device, including a biomass cracking unit, a nano zero-valent iron preparation unit and a loading unit;
[0078] S4.2, sending the biomass raw material into a cracking unit for cracking to obtain biochar;
[0079] S4.3, sending the biochar into the nano zero-valent iron preparation unit for loading to obtain a composite material;
[0080] S4.4. Perform subsequent processing on the composite material, including drying and curing.
[0081] From the above, it can be seen that the continuous preparation technology integrates the steps of biochar cracking, nano zero-valent iron preparation and loading, which significantly improves the production efficiency. This continuous preparation method avoids the waiting and transportation time between the steps in the traditional preparation method, making the entire preparation process more compact and efficient; at the same time, continuous preparation can also maintain the consistency of preparation conditions, which is conducive to ensuring the stability and quality of the composite material, and further enhancing its application effect in removing radioactive nuclides from aquatic products.
[0082] The effects of the biochar-zero-valent iron composite material for efficiently removing radionuclides from aquatic products in this embodiment and the biochar-zero-valent iron composite materials currently on the market were compared to obtain the following table:
[0083]
[0084]
[0085] It can be seen from the above table that the biochar-zero-valent iron composite material of the present invention is superior to the common biochar-zero-valent iron composite materials on the market in terms of specific surface area, pore volume, average pore size, radionuclide removal efficiency, etc.; at the same time, the present invention also adopts advanced loading technology, new cracking technology and continuous preparation process to further improve the performance and production efficiency of the material; in terms of cost-effectiveness and environmental friendliness, the present invention also has significant advantages, and therefore has broader application prospects.
[0086] A method for preparing a biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products, using the above-mentioned biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products, comprising:
[0087] Step 1, preparation of biochar: First, wheat straw is selected as a biomass raw material, and cracked at 600-700°C for 2-3 hours; after the cracking is completed, the biochar is soaked in a 0.5-1M acid solution for 12-24 hours to remove impurities; then, the biochar is washed with distilled water until neutral, and dried at 80-105°C for 6-12 hours to obtain the prepared biochar;
[0088] Step 2, preparation of nano zero-valent iron: Mix ferrous sulfate solution and carboxymethyl cellulose solution in a certain proportion. Carboxymethyl cellulose, as a stabilizer, helps prevent the agglomeration of nano zero-valent iron particles. Subsequently, under nitrogen protection, slowly add sodium borohydride solution for reduction reaction to generate nano zero-valent iron. During the reaction, continuous stirring is required to ensure the uniform generation of nano zero-valent iron, while controlling the reaction temperature and speed to obtain the ideal nanoparticle size and distribution. In addition, in order to further improve the stability and activity of nano zero-valent iron, an appropriate amount of reducing agent or surface modifier, such as polyvinyl pyrrolidone (PVP), can be added to the reaction system to optimize the performance of nano zero-valent iron;
[0089] Step 3: Nano-zero-valent iron is loaded on biochar: the prepared biochar is added to a mixed solution of ferrous sulfate and carboxymethyl cellulose, mixed evenly, and then a sodium borohydride solution is added dropwise; under continuous stirring, nitrogen is introduced for 30 to 60 minutes and then stopped, and the reaction is sealed for 60 to 90 minutes; thereafter, the mixture is allowed to stand at room temperature of 20 to 25°C in the dark for 6 to 12 hours, and the biochar-nano-zero-valent iron composite material is separated by magnetic separation;
[0090] Step 4. Preparation of multi-level structure composite materials: In order to increase the specific surface area and pore volume of the composite material and enhance its adsorption capacity for radioactive nuclides, a layer of mesoporous material is first loaded on the surface of the biochar. Select mesoporous materials with excellent pore structures such as silica and alumina, and evenly coat them on the surface of the biochar by sol-gel, impregnation or chemical vapor deposition. Subsequently, chemical or physical methods (such as co-precipitation, impregnation reduction, etc.) are used to load nano zero-valent iron on the mesoporous material to form a multi-level structure composite material. This multi-level structure not only increases the specific surface area and pore volume of the composite material, but also improves the dispersibility and stability of nano zero-valent iron through the confinement effect of the mesoporous material, thereby improving the overall performance of the composite material;
[0091] Step 5. Application of gradient loading technology: In order to further improve the removal efficiency of composite materials for radionuclides of different sizes and types, gradient loading technology is used. First, disperse the biochar in an appropriate solvent (such as ethanol, water, etc.) to form a uniform suspension. Then, gradually add nano zero-valent iron solutions of different concentrations, and control the addition speed and stirring conditions to make the nano zero-valent iron present a gradient distribution on the biochar. This gradient distribution can more effectively utilize the pore structure of biochar and the reduction properties of nano zero-valent iron to carry out targeted removal of radionuclides of different sizes and types. After the loading is completed, the composite material is dried and cured to improve its stability and durability;
[0092] Step six, preparation and loading of bimetallic nanoparticles: In order to improve the catalytic activity of nano zero-valent iron and its ability to reduce radioactive nuclides, other metal elements (such as palladium, nickel, etc.) are introduced to form bimetallic nanoparticles. First, an appropriate amount of metal salt solution (such as palladium salt, nickel salt, etc.) is evenly mixed with ferrous sulfate solution. Then, under nitrogen protection, the mixed solution is reacted with carboxymethyl cellulose solution and sodium borohydride solution to prepare bimetallic nanoparticles. During the reaction, the reaction conditions and metal ratios need to be precisely controlled to obtain the ideal bimetallic nanoparticle structure. After preparation, the bimetallic nanoparticles are loaded on biochar by physical or chemical methods to form a composite material with the ability to efficiently remove radioactive nuclides. This bimetallic nanoparticle not only improves the catalytic activity of the composite material, but also enhances its ability to reduce and remove radioactive nuclides through a synergistic effect;
[0093] Step 7: Surface modification of nano zero-valent iron: In order to prevent the aggregation of nano zero-valent iron and improve its dispersibility and stability in aquatic products, the nano zero-valent iron is surface modified; a suitable surfactant or polymer (including sodium dodecyl sulfate and polyvinyl alcohol) is selected and dissolved in an appropriate solvent, mixed evenly with the nano zero-valent iron solution and loaded on the biochar;
[0094] Step 8: Prepare biochar using new pyrolysis technology: In order to improve the performance of biochar, plasma pyrolysis or laser pyrolysis technology is used to prepare biochar; biomass raw materials such as bamboo and corn stalks are selected for pyrolysis, and the obtained biochar is characterized to determine its elemental composition and structural characteristics;
[0095] Step 9. Application of continuous preparation technology: In order to improve production efficiency, the steps of biochar cracking, nano zero-valent iron preparation and loading are integrated together for continuous preparation; design and build a continuous preparation device, including a biomass cracking unit, a nano zero-valent iron preparation unit and a loading unit, to achieve continuous production of composite materials.
[0096] Working principle: The composite material is composed of biochar and nano-zero-valent iron loaded thereon. The high specific surface area and rich pore structure of biochar are used to provide a large number of adsorption sites, combined with the strong reducing property of nano-zero-valent iron, to efficiently adsorb and reduce and remove radioactive nuclides in aquatic products. Through continuous preparation technology, the steps of biochar cracking, nano-zero-valent iron preparation and loading are integrated to improve production efficiency, ensure the stability and quality of the composite material, and thus achieve efficient and rapid removal of radioactive nuclides in aquatic products.
[0097] Furthermore, the preparation method of the biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products in this embodiment is compared with the current traditional method for removing radioactive nuclides from aquatic products, and the following table is obtained:
[0098]
[0099] It can be seen from the above table that the biochar-zero-valent iron composite material and the preparation method thereof of the present invention are superior or significantly superior to traditional methods in terms of processing efficiency, operating cost, environmental impact and raw material source; the method of the present invention not only achieves efficient removal of radioactive nuclides in aquatic products, but also reduces operating costs, reduces environmental impact, and has a wide range of raw material sources and low costs, and has significant technical advantages and broad application prospects.
[0100] Application example: The biochar-zero-valent iron composite material prepared in the above embodiment is used to efficiently remove cesium-137 and strontium-90 in aquatic products for multiple times (no less than 10 times), and the steps include:
[0101] Step 1: Mix aquatic product samples (including fish, shellfish, etc.) contaminated by cesium-137 and strontium-90 with biochar-nano zero-valent iron composite materials in a certain proportion to ensure that the composite materials are fully exposed to the radioactive nuclides in the aquatic products;
[0102] Step 2: standing at room temperature for a period of time (24 hours) to allow the composite material to fully adsorb and reduce the radioactive nuclides in the aquatic product;
[0103] Step 3: Separate the composite material from the aquatic product by physical methods (including filtration, centrifugation, etc.), and test the radionuclide content of the separated aquatic product to evaluate the removal effect.
[0104] From the above, it can be seen that the biochar-nano zero-valent iron composite material prepared by this technical solution shows a high efficiency in removing cesium-137 and strontium-90 in aquatic products. The experimental results show that the removal efficiency of the composite material for radioactive nuclides reaches more than 90%, which is significantly better than the traditional method.
[0105] In summary: In view of the high efficiency, low cost and environmental friendliness of this technical solution, it has broad application prospects in the fields of aquatic product processing, environmental monitoring around nuclear power facilities, etc. In particular, when dealing with radionuclide contamination incidents, this technical solution can be used as a fast and effective emergency treatment method.
[0106] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products, characterized by: The composite material consists of biochar and nano zero-valent iron loaded on the biochar, wherein the biochar is prepared by cracking wheat straw at 600-700°C for 2-3 hours, then soaking in a 0.5-1M acid solution for 12-24 hours, washing with distilled water until neutral, and drying at 80-105°C for 6-12 hours, and the nano zero-valent iron is prepared by reacting a ferrous sulfate solution with a carboxymethyl cellulose solution and a sodium borohydride solution under nitrogen protection, and loaded on the biochar. The specific surface area of the composite material is 6-12 m 2 / g, pore volume is 0.01~0.04cm 3 / g, and the average pore size is 8-15nm.
2. The biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products as claimed in claim 1, characterized in that: The nano zero-valent iron is loaded on the biochar by the following steps: adding a carboxymethyl cellulose solution to a ferrous sulfate solution, adding the biochar after uniform mixing, and then dropping a sodium borohydride solution, introducing nitrogen for 30 to 60 minutes under continuous stirring conditions and then stopping the nitrogen introduction, sealing the reaction for 60 to 90 minutes and then stopping the stirring, standing in the dark at room temperature of 20 to 25° C. for 6 to 12 hours, and separating the biochar nano zero-valent iron composite material by a magnetic separation method.
3. The biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products as claimed in claim 1, characterized in that: A layer of mesoporous material is first loaded on the surface of biochar, and then nano-zero-valent iron is loaded on it to enhance the adsorption capacity of radionuclides; At the same time, by adopting gradient loading technology, the distribution of nano zero-valent iron on biochar shows a gradient change.
4. The biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products as claimed in claim 1, characterized in that: Introducing other metal elements into nano-zero-valent iron to form bimetallic nanoparticles; At the same time, the surface of nano zero-valent iron is modified, including using surfactants and polymers.
5. The biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products as claimed in claim 1, characterized in that: The biochar is prepared by adopting a novel pyrolysis technology, and by introducing plasma pyrolysis and laser pyrolysis technology, biochar with special structure and performance, including high specific surface area and high porosity, is prepared.
6. The biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products as claimed in claim 1, characterized in that: The composite material is prepared by using a continuous preparation technology, integrating the cracking of biochar, the preparation of nano zero-valent iron and the loading steps.
7. A method for preparing a biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products, characterized in that: A biochar-zero-valent iron composite material for efficiently removing radioactive nuclides from aquatic products according to any one of claims 1 to 6, comprising: Step 1: First, wheat straw is selected as a biomass raw material and cracked at 600-700°C for 2-3 hours; after the cracking is completed, the biochar is soaked in a 0.5-1M acid solution for 12-24 hours to remove impurities; then, the biochar is washed with distilled water to neutrality and dried at 80-105°C for 6-12 hours to obtain the prepared biochar; Step 2: Evenly mix the ferrous sulfate solution and the carboxymethyl cellulose solution, and then drop the sodium borohydride solution under nitrogen protection to react and generate nano zero-valent iron; continuous stirring is required during the reaction to ensure uniform generation of nano zero-valent iron; Step 3: Add the prepared biochar to the mixed solution of ferrous sulfate and carboxymethyl cellulose, mix evenly, and then drop the sodium borohydride solution; under continuous stirring, introduce nitrogen for 30 to 60 minutes and then stop introducing nitrogen, seal and react for 60 to 90 minutes; then, stand at room temperature 20 to 25°C in the dark for 6 to 12 hours, and separate the biochar-nano zero-valent iron composite material by magnetic separation; Step 4: In order to increase the specific surface area and pore volume of the composite material, a layer of mesoporous material is first loaded on the surface of the biochar, and then nano-zero-valent iron is loaded thereon; the loading of nano-zero-valent iron on the mesoporous material is achieved by chemical or physical methods to form a multi-layered composite material; Step 5: In order to further improve the removal efficiency of the composite material for radionuclides of different sizes and types, a gradient loading technology is used; the biochar is dispersed in an appropriate solvent to form a suspension, and nano zero-valent iron solutions of different concentrations are gradually added to make the nano zero-valent iron present a gradient distribution on the biochar; the composite material is then dried and cured; Step 6: In order to improve the catalytic activity of nano zero-valent iron and its ability to reduce radioactive nuclides, other metal elements are introduced into the nano zero-valent iron to form bimetallic nanoparticles; after evenly mixing an appropriate amount of metal salt solution and ferrous sulfate solution, the bimetallic nanoparticles are reacted under nitrogen protection to prepare bimetallic nanoparticles, and the bimetallic nanoparticles are loaded on biochar; Step 7: To prevent the aggregation of nano-zero-valent iron and improve its dispersibility and stability in aquatic products, the nano-zero-valent iron is surface modified; a suitable surfactant or polymer is selected and dissolved in an appropriate solvent, mixed evenly with the nano-zero-valent iron solution, and then loaded on the biochar; Step 8: To improve the performance of biochar, plasma pyrolysis or laser pyrolysis technology is used to prepare biochar; biomass raw materials such as bamboo and corn stalks are selected for pyrolysis, and the obtained biochar is characterized to determine its elemental composition and structural characteristics; Step 9: In order to improve production efficiency, the steps of biochar cracking, nano-zero-valent iron preparation and loading are integrated together for continuous preparation; design and build a continuous preparation device, including a biomass cracking unit, a nano-zero-valent iron preparation unit and a loading unit.
Citation Information
Patent Citations
Nanometer zero-valent iron-biochar composite material, and preparation method and application thereof
CN108911005A
Biochar nanoscale zero-valent iron composite material and preparation method and application thereof
CN110385110A
Method for removing hexavalent chromium in water by using biochar-loaded nanometer iron-nickel composite material
CN110745935A